Speed-accuracy manipulations and diffusion modeling: lack of discriminant validity of the manipulation or of the parameter estimates? - Lerche, Veronika; Voß, Andreas (Behavior research methods, 2018)
The diffusion model (Ratcliff, 1978) is a mathematical model theorized to untangle different cognitive processes involved in binary decision tasks. To test the validity of the diffusion model parameters, several experimental validation studies have been conducted. In these studies, the validity of the threshold separation parameter was tested with speed-accuracy manipulations. Typically, this manipulation not only results in the expected effect on the threshold separation parameter but it also impacts nondecision time: Nondecision time is longer in the accuracy than in the speed condition. There are two possible interpretations of the finding: On the one hand, it could indicate that speed versus accuracy instructions really have an impact on the duration of extradecisional processes. On the other hand, the effect on the measure for nondecision time could be spurious—that is, based on a problem in the parameter estimation procedures. In simulation studies—with the parameter sets based on typical values from experimental validation studies—we checked for possible biases in the parameter estimation. Our analyses strongly suggest that the observed pattern (i.e., slower nondecision processes under accuracy instructions) is attributable to a lack of discriminant validity of the manipulation rather than to trade-offs in the parameter estimations.
Gesehen am 06.03.2019